ETHNOMATHEMATICAL EXPLORATION IN THE BUILDING OF THE GLASS BUILDING OF THE PALACE OF YOGYAKARTA - Faizah, Hilmy (Tesseract: International Journal of Geometry and Applied Mathematics, 2023)
Ethnomatematics has an important role in learning mathematics. Ethnomatematics can make learning mathematics more meaningful because it is related to problems that exist around students. An example of a place steeped in history and culture is the Yogyakarta Palace. Inside the Yogyakarta Palace there are various buildings, one of which is Gedhong Kaca. This study aims to explore the mathematical concepts contained in the Gedhong Kaca building at the Yogyakarta Palace. The method used in this study is explorative with an ethnographic approach. Data collection was carried out by means of observation, documentation, and literature study. The results obtained show that there are several mathematical concepts in the Gedhong Kaca building that can be used in learning mathematics, namely the concept of triangles, quadrilateral concepts, circle concepts, space concepts, straight line concepts, congruence concepts, congruence concepts, and geometric transformation concepts